Scoping Review HIV pada Remaja di Indonesia - Sulis Puspito Rini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Sexually transmitted infections or STIs are types of infections that are spread through sexual intercourse, such as vaginal, oral, or anal sex. Human Immunodeficiency Virus (HIV) attacks the human immune system and can cause Acquired Immune Deficiency Syndrome (AIDS), a disease that can weaken the immune system and cause opportunistic. This research design uses a scoping review. A literature review is one way of research using review and reviews. This research, conducted by examining articles on Google Scholar was examined. This literature review has screened articles from one database of 200 articles, then found 10 selected articles. Furthermore, the authors found themes in this literature review, among others, HIV services in adolescents and two themes were factors related to HIV screening in adolescents, namely sociodemographic factors and health factors. Researchers concludes that HIV can be transmitted through promiscuity and sexual activities that do not use contraceptive.